A Simple Energy Recovery Scheme To Harvest The Energy From Shaded Photovoltaic Modules During Partial Shading - Ramli, Mohd Zulkifli; Salam, Zainal (IEEE, 2014)
This paper proposes a simple circuit to recover the energy that otherwise would be lost due to the partial shadings on photovoltaic (PV) modules.Since the circuit can be readily retrofitted to an existing PV system,no modification on the central inverter is required.The main idea of the scheme is that,during partial shading,parts of the current from the nonshaded modules are harvested by an energy recovery circuit using power electronic switches and storage components.In doing so,the current of the PV string is maintained at the level generated by the shaded module.There is no need for the shaded module to be short-circuited;as a result,it can still actively produce output power (despite being partially shaded).To investigate the idea,the proposed circuit is retrofitted to a prototype PV system using eight modules.The partial shading conditions are emulated using a solar simulator with a controllable irradiance capability.The results are validated by a good agreement between the experimental and simulation works